Erratum: Avian haemosporidian infections in rufous-collared sparrows in an Andean dry forest: diversity and factors related to prevalence and parasitaemia (Parasitology (2022) DOI: 10.1017/S0031182018002081) - Cadena-Ortiz, Héctor (2022)
The following error in Table 1 has come to the authors’ attention: Current information: BAEBIC02 (GenBank: KF537291) Correct information: BAEBIC02 (GenBank: KF537287) The corrected version of the Table is shown below, with the corrected information in bold: (Table presented) In addition, Figure 2 also contains errors: Current information: P. homopolare KF537281 ZOCAP11 BAEBIC02; P. homopolare KF537291 ZOCAP12 BAEBIC02 (grey shading) Correct information: P. homopolare KF537287 BAEBIC02; P. homopolare KF537291 ZOCAP12 (no grey shading, because this lineage was not found in the authors’ sample). The corrected version is shown below: Finally, throughout the manuscript, ZOCAP15 should read ZONCAP15. (Figure presented).